The complete chloroplast genome sequence of Michelia compressa - Dongqin Zhou; Shipeng Lu; Zhaoqi Hou; Jinping Yu (Mitochondrial DNA. Part B. Resources, 2020)
Michelia compressa is an evergreen ornamental tree species. The high-throughput sequencing technology was used to sequence and assemble the chloroplast genome of Michelia compressa. Results showed that the chloroplast genome is 160,061 bp in length, of which the inverted repeats sequence (IRs) is 26,581 bp, the large single-copy region (LSC) and the small single copy region (SSC) are 88,097 bp and 18,802 bp, respectively. The GC content of the plastome was 39.2%, with 43.2%, 37.9% and 34.2% in IRs, LSC and SSC, respectively. A total of 132 genes are annotated, 86 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. This study enriched the Michelia compressa genomic information which provides the basis for rational exploitation and utilization of germplasm resources.